FORMATION OF NATIONAL SELF-CONSIOUSNESS OF STUDENTS IN THE CLASSROOM OF A FOREIGN LANGUAGE - Tilyakhodzhaeva F.M (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article talks about the ways and possibilities of forming students' self-awareness in foreign language classes, as well as using authentic language material for this purpose. Particularly emphasized is the need to use new teaching aids created during the acquisition of state independence by Uzbekistan.